Water productivity in the biosynthesis of Origanum vulgare L. essential oil and biomass - Thaner dos Santos, Hugo; Alcarde Sermarini, Renata; Alejandra Moreno-Pizani, Maria; Angélica Alves Marques, Patricia (Polish Journal of Agronomy, 2023)
Oregano biomass and essential oil can be used in human and animal nutrition, as well as in medicines’ production. Thus, it is necessary adopting rational water use in oregano production and accounting this use based on the water productivity index to achieve proper irrigation management in oregano culture. Two experiments were carried out at 4×3+1 factorial arrangement, and 4 potential soil water matrices , 3 oregano phenological stages and 1 control treatment (soil at field capacity) were assessed. Based on the recorded results, water productivity in oregano culture is influenced by both cultivation season and deficient irrigation throughout the whole cultivation cycle, rather than just at some specific phenological stage. The best water productivity index based on essential oil biosynthesis was recorded when irrigation was managed at -60.8 kPa soil water matric po- tential (spring/summer). On the other hand, the best water productivity index due to dry biomass was recorded when irrigation management was carried out at -91.2 kPa (at both seasons)